Lamb Temporal Bone as a Surgical Training Model of Round Window Cochlear Implant Electrode Insertion. Issue 1 (January 2016) - Mantokoudis, Georgios; Huth, Markus E.; Weisstanner, Christian; Friedrich, Hergen M.; Nauer, Claude; Candreia, Claudia; Caversaccio, Marco D.; Senn, Pascal
Abstract : Objective: The preservation of residual hearing in cochlear implantation opens the door for optimal functional results. This atraumatic surgical technique requires training; however, the traditional human cadaveric temporal bones have become less available or unattainable in some institutions. This study investigates the suitability of an alternative model, using cadaveric lamb temporal bone, for surgical training of atraumatic round window electrode insertion. Intervention: A total of 14 lamb temporal bones were dissected for cochlear implantation by four surgeons. After mastoidectomy, visualization, and drilling of the round window niche, an atraumatic round window insertion of a Medel Flex24 electrode was performed. Electrode insertion depth and position were verified by computed tomography scans. Main Outcome Measure: All cochleas were successfully implanted using the atraumatic round window approach; however, surgical access through the mastoid was substantially different when compared human anatomy. The mean number of intracochlear electrode contacts was 6.5 (range, 4–11) and the mean insertion depth 10.4 mm (range, 4–20 mm), which corresponds to a mean angular perimodiolar insertion depth of 229 degrees (range 67–540°). Full insertion of the electrode was not possible because of the smaller size of the lamb cochlea in comparison to that of the human. Conclusion: The lamb temporal bone model is well suited as a training model for atraumatic cochlear implantation at the level of the round window. The minimally pneumatized mastoid as well as the smaller cochlea can help prepare a surgeon for difficult cochlear implantations. Because of substantial differences to human anatomy, it is not an adequate training model for other surgical techniques such as mastoidectomy and posterior tympanotomy as well as full electrode insertion.